Unresolved issues in the understanding of the pathogenesis of local tissue damage induced by snake venoms. (15th June 2018) - Gutiérrez, José María; Rucavado, Alexandra; Escalante, Teresa; Herrera, Cristina; Fernández, Julián; Lomonte, Bruno; Fox, Jay W.
Abstract: Snakebite envenoming by viperid species, and by some elapids, is characterized by a complex pattern of tissue damage at the anatomical site of venom injection. In severe cases, tissue destruction may be so extensive as to lead to permanent sequelae, with serious pathophysiological, social and psychological consequences. Significant advances have been performed in the study of venom-induced tissue damage, including identification and characterization of the toxins involved, insights into the mechanisms of action of venoms and toxins, and study of tissue responses to venom-induced injury. Nevertheless, much remains to be known and understood on the pathogenesis of these alterations. This review focuses on some of the pending issues in the topic of snake venom-induced local tissue damage. The traditional 'reductionist' approach, which has predominated in the study of snake venoms and their actions, needs to be complemented by more integrative and holistic perspectives aimed at capturing the complexity of these pathological alterations. Future advances in the study of these topics will certainly pave the way for innovative therapeutic interventions, with the goal of reducing the impact of this aspect of snakebite envenoming. Graphical abstract: Local tissue damage induced by snake venoms. Highlights: The main aspects of snake venom-induced local pathology are reviewed. The main unresolved issues for understanding venom-induced local pathology are discussed. The roles of venom toxins and of endogenous host responses are analyzed. A more integrated and holistic approach to this subject is needed.